Medical image recognition, segmentation and parsing : machine learning and multiple object approaches - Zhou, S. Kevin (Elsevier, 2016)
This book describes the technical problems and solutions for automatically recognizing and parsing a medical image into multiple objects, structures, or anatomies. It gives all the key methods, including state-of-the-art approaches based on machine learning, for recognizing or detecting, parsing or segmenting, a cohort of anatomical structures from a medical image. You will learn how to: research challenges and problems in medical image recognition, segmentation and parsing of multiple objects; methods and theories for medical image recognition, segmentation and parsing of multiple objects; efficient and effective machine learning solutions based on big datasets; selected applications of medical image parsing using proven algorithms. -- Edited summary from book.
Keywords: Imaging systems in medicine.; Machine learning.; Image reconstruction.; Pattern recognition systems.; elektronické knihy; electronic books